PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM BINA MARGA PROVINSI SUMATERA SELATAN - Danila, Danila; Kore, Jefirtson R Riwu (Universitas Indo Global Mandiri Palembang, 2019)
This study discusses competency and motivation for performance in the Public Works Agency of the Highways of South Sumatra Province. The results of this study prove that the dimensions of competence have a significant effect on improving employee performance at the Public Works Agency of the Highways of South Sumatra Province. This can be proven from the results that can be verified between t count = 3.63 and t table = 2.95. Then the motivation dimension to the performance of employees in the Public Works Agency of Highways of South Sumatra Province does not show more dominant variables on employee performance, this is because the motivation variable has a value of tcount = 2.201 <t table = 2.95.Keywords: Competence, Motivation, Performance, Public Works Agency